Analysis of Immunization Services During The Covid-19 Pandemic - Fithriany; Cut Yuniwati (Institute of Computer Science (IOCS), 2022)
The immunization program launched by the Ministry of Health is one of the preventive measures to avoid contracting certain diseases, namely preventable diseases by immunization including tuberculosis, diphtheria, pertussis, tetanus, hepatitis B, polio and measles. The Covid-19 pandemic threatens to have an impact on health progress and in particular on child development due to the delay in immunization services as a national program. The purpose of this Systematic Review is to analyze the effect of immunization services during the Covid-19 pandemic. Database search includes Google Scholar, Science Direct, and Pubmed with keywords The keywords used are complete basic immunization, covid-19 period, impact of COVID-19 immunization. The next stage is to select articles according to the criteria, which are published in 2017-2022 with the full text of 12 articles that meet the inclusion criteria. Initial literature search found 52 articles (Google Schoolar 42 articles, Science Direct 10 articles, Proquest 5 articles) 40 articles issued were not in sync with the topic of discussion and did not discuss complete basic immunization 12 full text articles met the criteria. Immunization should be prioritized to prevent and protect from preventable diseases by immunization during the Covid-19 pandemic, if the situation allows. Basic immunization services during the Covid-19 pandemic decreased and affected the amount of immunization coverage. Factors that influence this are the main focus of health services on Covid-19 cases, the implementation of lockdown, physical-social distancing, self-isolation and delays in the distribution of vaccine supplies